Star Pylon, New York World's Fair (Curt Teich & Co.)
The Star Pylon, a great shaft of varnished wood reaching approximately 130 feet inot the air, is located at the northern end of the Communications Bulding near the Long Island Railroad Station. Its natural wood finish, and its unusual size make it one of the most attention-compelling structures in the Fair. It is fitted with tube lighting behind shields, and the light, directed on the deeply-fluted varnished wood surface, gives an unusual and pleasing illumination to the whole tower at night. The pylon is made of Douglas fir.